Global attractors for non-linear viscoelastic equation with strong damping - Ma, Zhiyong (Nonlinear Analysis: Modelling and Control, 2013)
In this paper, we consider the long-time dynamical behavior of the viscoelastic equations with strong damping and further prove the existence of global attractors for this system.
Keywords: attractors; viscoelastic; damping